Observer agreement comparing the use of virtual slides with glass slides in the pathology review component of the POSH breast cancer cohort study. Issue 5 (23rd March 2012) - Shaw, Emily Clare; Hanby, Andrew M; Wheeler, Kevin; Shaaban, Abeer M; Poller, David; Barton, Sheila; Treanor, Darren; Fulford, Laura; Walker, Rosemary A; Ryan, Deirdre; Lakhani, Sunil R; Wells, Clive A; et al.
Abstract : Aims: (1) To compare the use of scanned virtual slide images (virtual microscopy) with glass slides (conventional microscopy) in the assessment of morphological characteristics of breast cancers within the setting of the Prospective study of Outcomes in Sporadic versus Hereditary breast cancer (POSH), involving a cohort of women under 40 years of age, presenting with breast cancer. (2) To assess the acceptability to histopathologists of the use of virtual slide images. Methods: 13 histopathologists from the UK and Australia participated in the POSH pathology review. The observers were asked to assess multiple morphological features such as tumour grade and type. Comparisons were made for a single observer using both virtual images and glass slides. Intra- and inter-observer variability was calculated using the κ statistic and a comparison was made between the use of each image modality. Results: Diagnostic performance with virtual slides was comparable to conventional microscopic assessment, with the measurement of agreement best for vascular invasion, necrosis and the presence of a central scar (κ=0.37–0.78), and poor for more subjective parameters such as pleomorphism, stroma, the nature of the tumour border and the degree of lymphocytic infiltrate (κ=0.1). Conclusion: Virtual slides represent an acceptable methodology for central review of breast cancer histopathology and can circumvent the need for either travel to view material, or the potential problems of sending it by post.